Search In
• More options...
Find results that contain...
Find results in...

# Maths problem that I shouldn't be having so much difficulty with

16 minutes ago, LOUOS said:

U = K-      P                   This is the original expression and the task was to rearrange to make D the subject.

3D-Y

-K

(U-K)=    -P

3D-Y

*(3D-Y)

(U-K)(3D-Y)=-P

3DU-3DK-UY+KY=-P

this is as far as I have been able to get so far. If its obvious to you what to do next would you mind explaining rather that commenting the answer with some hilarious quip like "git gud".

You were like 1 or 2 steps off, I always used to forget this. move every factor with D onto the same side on their own so you have

3DU-3DK=....

factorise that side to

D(3U-3K)=...

then divide it all by that factor so you are left with B. this is what I beleive it is

D=-P+UY-KY/3U-3K

thing

## Recommended Posts

Posted · Original PosterOP

U = K-      P                   This is the original expression and the task was to rearrange to make D the subject.

3D-Y

-K

(U-K)=    -P

3D-Y

*(3D-Y)

(U-K)(3D-Y)=-P

3DU-3DK-UY+KY=-P

this is as far as I have been able to get so far. If its obvious to you what to do next would you mind explaining rather that commenting the answer with some hilarious quip like "git gud".

temporary solution - someone else's problem

##### Share on other sites
5 minutes ago, LOUOS said:

U = K-      P                   This is the original expression and the task was to rearrange to make D the subject.

3D-Y

-K

(U-K)=    -P

3D-Y

*(3D-Y)

(U-K)(3D-Y)=-P

3DU-3DK-UY+KY=-P

this is as far as I have been able to get so far. If its obvious to you what to do next would you mind explaining rather that commenting the answer with some hilarious quip like "git gud".

You only have D left on the left hand side, multiplying two terms. Combine them, so D multiplies a difference (3U-3K). Move anything adding or subtracting to the right hand side with proper signs, then divide by (3U-3K).

You can also resume from your 3rd step: instead of distributing everything, you can go for

3D-Y = -P/(U-K)

D =    -P      +   Y

3(U-K)      3

With that in mind, I advice you to use my first paragraph to continue from your 4th line, and try to get to D = -P/3(U-K)+Y/3 from there as practice.

##### Share on other sites
16 minutes ago, LOUOS said:

U = K-      P                   This is the original expression and the task was to rearrange to make D the subject.

3D-Y

-K

(U-K)=    -P

3D-Y

*(3D-Y)

(U-K)(3D-Y)=-P

3DU-3DK-UY+KY=-P

this is as far as I have been able to get so far. If its obvious to you what to do next would you mind explaining rather that commenting the answer with some hilarious quip like "git gud".

You were like 1 or 2 steps off, I always used to forget this. move every factor with D onto the same side on their own so you have

3DU-3DK=....

factorise that side to

D(3U-3K)=...

then divide it all by that factor so you are left with B. this is what I beleive it is

D=-P+UY-KY/3U-3K

thing

##### Share on other sites
Posted · Original PosterOP

thanks 1_thing and SpaceGhostC2C this helped alot.

temporary solution - someone else's problem